Factors Affecting the Survival of Auxotrophs and Prototrophs of Saccharomyces cerevisiae in Mixed Populations - Moat, Albert G. (1966)
Moat, Albert G. (Hahnemann Medical College, Philadelphia, Pa.), Isabel J. Barnes, and Eleanor H. McCurley. Factors affecting the survival of auxotrophs and prototrophs of Saccharomyces cerevisiae in mixed populations. J. Bacteriol. 92:297–301. 1966.—The conditions under which the number of yeast prototrophs, as well as respiration-deficient mutants, could be materially decreased, while allowing the survival of auxotrophic mutants in recoverable numbers, have been investigated in detail. Neither the use of carbohydrates other than glucose to prevent development of respiration-deficient mutants, nor treatment with acriflavine to render all surviving wild types respiration-deficient, provided a selective advantage for the auxotrophs. Increased concentrations of the antifungal agents amphotericin B or endomycin, while reducing the number of respiration-deficient mutants, did not significantly increase the final mutant-wild type ratio. A more soluble form of amphotericin B (Fungizone), when used under carefully defined physiological conditions, produced a significant reduction in the number of surviving prototrophs relative to the surviving auxotrophs, without development of respiration-deficient mutants.